Pemberdayaan Kelompok Remaja Melalui Pelatihan Desain di Kampung Jimpitan Kelurahan Batu Jaya Kota Tangerang - Pangestu, Ilham Aji; Kurniawan, Irvan Arif; Nasution, Muhammad Amin; Latif, Inas Sofia; Fikri, Sudana (LP2M INSURI Ponorogo, 2023)
Youth activities in Jimpitan Village in RT 03 RW 03, Batu Jaya, Batu Ceper, Tangerang City are gathered in a forum known as PIKKR (Center for Information, Counseling, Youth Communication). Based on the results of the interview, it is known that the problem faced by the PIKKR youth group is the productivity of the adolescent group in developing and optimizing existing resources. The purpose of implementing this PKM is to empower and develop the potential of PIKKR in the development of Jimpitan Village. Empowerment and development are carried out in the form of design training. The method was carried out with Participatory Action Research (PAR) to the PIKKR youth group. Based on the PKM that has been implemented, it can be concluded that, first, participants' interest in exploring design, participants' understanding of adobe illustrator applications, and understanding of the use of pathfinders show a positive trend. However, in terms of interest in studying adobe illustrator applications shows doubts. Second, participants already understand the basics and theories in the design. Third, participants can already practice these design theories by making design samples. As for the advice given, first, a special space was created that can be used as a design practice for PIKKR teenagers. Second, there are continuous follow-up activities, in the form of advanced training and intensive mentoring.